Membincang Keadilan Tuhan (Teodise) dalam Bencana Tsunami di Aceh - Bagir, Haidar (Unisia, 2016)
Earthquake that happens at Aceh Provinve currently appears question mark: what will God do? Why The Beneficent and the Merciful God creates disaster and tsunami? Instead, this disaster causes many people died as the victims. Those issues contain the books of theology, whenhuman knows religion and Greek philosophy. Why earth quake happens at Aceh? Certainly some people regard as waming or punishment especially for Acehnese on one hand and on the other hand they need the new generation birth because of the deadlock of their problem solution that without ending. This artide traces the problem solution from philosophical point of view.